Estudo da evolução dos padrões de comportamento reprodutivo de Cynolebiatini (Cyprinodontiformes - Rivulidae) - Belote, Drausio de Freitas (2001)
The reproductive behaviors of nineteen species of the Cynolebiatini are described in this study. The obtained data added to the literature data plus personal communications provided some ethological patterns. These patterns were optimized through strong phylogenetic trees based principally on morphological characters, in order to obtain the most parsimonious hypothesis of the evolution of these patterns at the species level and among genera. Initially, the reproductive behavior was divided into five distinct stages: 1) Courtship displays, 2) Invitation, 3) Submerging (to dig the substrate), 4) Spawning/fertilization, 5) Emerging ( comes back from the substrate ), where some patterns were established and optimized into preexistent phylogenies. The closed unpaired fns of the males during the courtship showed by S. similis + S. stellatus + Simpsonichthys sp. 2 is synapomorphic fr this group into the genus Simpsonichthys, but analyzing this condition fr Cynolebiatini it becomes homoplasic because also occurs in Nematolebias myersi. Other synapomorphies fr Simpsonichthys are: the absence of invitation fr S. similis + S. stellatus + Simpsonichthys sp. 2 and the absence of trembling during the invitation fr S. notatus + S. trilineatus. The presence of head- shakings, the exbition of slow lateral waving movements (or even the absence of it), the selection of a dominant fmale by the couple and the fmale scrubbing the male are considered synapomorphic fr C ynolebias. A synapomorphy of Nmatolebias is the absence of fight among the fmales. Some autapomorphies and undefned apomorphies were also observed.